Improving Fiqh Learning Outcome through Discussion Method on Qurban and Aqiqah Material in Class X MAN 2 Bandung - Mustopa, Aam Ridwan; Rahman, Alvin Yanuar (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The study aimed to improve the learning outcome of Fiqh (Islamic Jurisprudence) through the Discussion Method on Qurban and Aqiqah (Sacrifice and Aqiqah) material in Class X at MAN 2 Bandung. The research method utilized Classroom Action Research. The findings revealed that the teacher's activity scored 78 out of a maximum of 100, categorized as good, yet not optimal due to the predefined indicator score of 80. Similarly, students' activities scored 75, considered good but also below the preset indicator of 80. Test results showed an improvement in learning outcomes, with 80% of students achieving mastery. However, further improvement is needed as the minimum mastery percentage is not yet reached. The reflection highlighted the need for improvement in classroom management and student engagement. The study suggests providing incentives for cooperative group work and addressing classroom disruptions to enhance learning effectiveness.